A logarithmic CMOS image sensor with wide output voltage swing range - Campos, Fernando de Souza [UNESP]; Silva, Marcelo Macchi da; Bordon, Mario Eduardo [UNESP]; Swart, Jacobus W.; Murphy, R. S. (Ieee, 2017)
This paper presents logarithmic CMOS image sensor with wide output voltage swing range. Wide output voltage swing range is achieved by increasing the number of transistors connected as diodes of logarithmic CMOS image sensor. A prototype has been fabricated in 0.35 mu m AMS opto process. Four different pixels were fabricated using 20 mu mx20 mu m Nwel/Psub photodiodes with one, two, three and four transistors in series. The sensitivity measured were 136mV/Dec, 191mV/Dec, 281mV/Dec and 425mV/Dec for the pixels using one, two, three and four transistors in series respectively. This results shows that the sensitivity is increased by N approximately, were N is the number of transistors in series at pixels. Considering that the supply voltage the four- transistor pixel presents total output voltage swing range of 2.65V over a range of 120dB being the supply voltage 3.3V.
Keywords: CMOS; high sensitivity; logarithmic pixel; photodetector